the Exploring the Literary Representation of Trauma-Generated Dissociation in the personality of the protagonist of Hassan Blasim’s The Nightmares of Carlos Fuente - Abdulemam , Lec.Dr. Maher Abdulhameed (Thi Qar Arts Journal, 2024)
The current research deals with the conceptualization of trauma-generated dissociation in the personality of the protagonist of Hassan Blasim’s The Nightmares of Carlos Fuentes. The research adheres to the theory of trauma and dissociation of Sigmund Freud, Pierre Janet, and Cathy Caruth. It employs some of their psychological notions including identity fragmentation, pathogenetic reminiscences, traumatic neurosis, vehement emotions, speechless terror, latency period, and incubation to the personality of the protagonist of the story. The research concludes that traumatic events of war and violence in Iraq lead Salim (Carlos Fuentes), the protagonist of the story, to experience dissociative behavior that results in vehement emotions, identity fragmentation, and traumatic neurosis, leading to his tragic death.